2015
DOI: 10.1134/s0016793214060218
|View full text |Cite
|
Sign up to set email alerts
|

The response of the ionosphere to the earthquake in Japan on March 11, 2011 as estimated by different GPS-based methods

Abstract: The results of detecting ionospheric disturbances by different methods based on GPS observations during the mega earthquake in Japan (March 11, 2011) are analyzed. It is shown that different methods of analysis and data processing technologies provide generally similar results and suggest quite a complex mor phology of the ionospheric response to this seismic event. We distinguish three types of wave disturbances that appeared in the ionosphere in response to the earthquake: slow gravity waves, acoustic-gravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…These suggested that the horizontal wavelength of the gravity waves following the 2011 Tohoku tsunamigenic earthquake ranged from 200 to 400 km. Yasyukevich et al [ 12 ] also indicated that the wavelength of the gravity waves induced by the 2011 Tohoku earthquake was ~200 km.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These suggested that the horizontal wavelength of the gravity waves following the 2011 Tohoku tsunamigenic earthquake ranged from 200 to 400 km. Yasyukevich et al [ 12 ] also indicated that the wavelength of the gravity waves induced by the 2011 Tohoku earthquake was ~200 km.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that three kinds of ionospheric disturbances were observed after the 2011 Tohoku tsunamigenic earthquake related to the source displacement, the Rayleigh waves, and the tsunami waves. The three kinds of ionospheric disturbances have different propagating speeds, which are associated with seismic Rayleigh waves (2.0–3.0 km/s), acoustic waves (0.3–1.5 km/s), and gravity waves (0.1–0.3 km/s) [ 5 , 9 , 11 , 12 , 30 , 33 ]. As studied by Galvan et al [ 30 ] and Jin et al [ 11 ], the most disturbed region after the 2011 tsunamigenic earthquake was located in the northwest part of the epicenter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method of mapping ionospheric disturbances, which has been repeatedly used for detecting TIDs [Perevalova et al, 2008;Tsugawa et al, 2011;Kunitsyn et al, 2011;Perevalova et al, 2012;Afraimovich et al, 2013;Astafyeva et al, 2013;Yasyukevich et al, 2015;Zakharov et al, 2016], has demonstrated its effectiveness in detection of local disturbances. We have identified relatively weak and vertically localized disturb-ances caused by the effect of the Progress spacecraft engine in the April 16, 2014 experiment.…”
Section: Resultsmentioning
confidence: 99%